Hubungan Pengetahuan Ibu Hamil, Gaya Hidup, Dan Pola Nutrisi Yang Mempengaruhi Terjadinya Anemia Pada Ibu Hamil Di Wilayah Kerja Puskesmas Picung Kabupaten Pandeglang Tahun 2022: The Relationship between Knowledge of Pregnant Women, Lifestyle, and Nutritional Patterns that Affect the Occurrence of Anemia in Pregnant Women in the Work Area of Picung Health Center Pandeglang Regency in 2022 - Karubuy, Milka Anggreni; Marwati, Santy Sofa (Dohara POAJ, 2023)
Introduction: The incidence of anemia in pregnant women continues to increase every year, from the results of research at the Picung District Health Center, Pandeglang Regency, the authors found several causal factors including knowledge of pregnant women, lifestyle, and nutritional patterns that are not balanced, so that this results in the incidence of anemia in pregnant women tends to increase. Methods: This type of research is quantitative research with the form of observational analytical research. The population in this study were pregnant women with anemia recorded in the working area of the Picung Health Center, Pandeglang Regency in 2022, a total of 59 pregnant women with anemia symptoms. The sample in this study was the entire population of pregnant women with anemia symptoms in the working area of the Picung Health Center, Pandeglang Regency namely 59 respondents. Results: There is a significant relationship between knowledge of pregnant women p-value (0,002); Lifestyle p-value = (0,002); and Nutritional Patterns p-value = (0,002) with anemia in pregnant women in the work area of the Picung Health Center, Pandeglang Regency in 2022. Discussion: The results of the study show a relationship between knowledge of pregnant women, lifestyle, and nutritional patterns that cause anemia in pregnant women in the working area of the Picung Public Health Center, Pandeglang Regency in 2022. The results of this study are expected to provide new information to respondents about the relationship between knowledge of pregnant women, lifestyle, and nutritional patterns that affect the occurrence of anemia in the Picung Health Center in Pandeglang Regency in 2022.